S Regional security integration and confidence-building between Iraq and the Gulf Arab states - MUSTAFA JABER FAYADH AL-ALWANI (Tikrit Journal For Political Science, 2026)
The research deals with the topic "regional security integration; confidence-building between Iraq and the Arab Gulf states" as a strategic tool; enhances regional stability; contributes to overcoming the costs of conflicts and some of the rivalries, especially the Arab Gulf, and comes to the main problem of research; with the question: "How does" security integration" build a regional environment; be more stable; at the expense of conflicts?" The main premise is that "security integration", if designed and implemented in accordance with a strategic vision, would be an effective alternative to" traditional alliances " and enhance the resilience of states in the face of the security challenges they face, including complex complex ones. The research seeks to achieve major goals, most notably: discussing the effectiveness of "security integration" and its feasibility, describing its challenges, and foreseeing future opportunities; to achieve it, the importance lies in its contribution to identifying practical approaches, especially decision makers, the research used three basic approaches: "descriptive analytical approach", "sometimes comparative approach", and in the areas of "case study approach", and others as well. The structure of the research was divided into chapters, which discussed: the theoretical framework of security integration, international and regional experiences, the most prominent security and technical challenges, future prospects and policies, and then practical recommendations for Iraq and the Gulf.